The OPTIMIZATION OF ADOLESCENT WOMEN'S PREPARATION IN FACING MENARCHE IN CISAYONG DISTRICT, TASIKMALAYA DISTRICT, 2023 - Kurnia, Herni; Rismawati, Sariestya; Laila Putri Suptiani (Poltekkes Kemenkes Tasikmalaya, 2024)
Menarche is the first menstruation that occurs and is one of the characteristics of a woman becoming an adult. Menarche tends to be earlier when the child has not yet reached mental maturity and also a lack of knowledge factors give rise to various psychological responses in girls when experiencing menarche. Knowledge about menstruation is needed by young women. The results of preliminary research and studies in Cisayong Village, Tasikmalaya Regency, found that all young women said that their mothers did not provide information about menstruation and they did not know complete care for menstruation. Based on a preliminary study conducted on adolescent girls aged 10-12 years at SDN 3 Cisayong, Tasikmalaya Regency, as many as 8 out of 10 female students had insufficient knowledge about menarche and menstruation. And based on interviews with teachers and school principals, they said that there had never been any information or counseling about menstruation among teenagers. The aim of this PKM is to optimize the preparation of young women in facing menarche and menstrual care at SDN 3 Cisayong, Tasikmalaya Regency by providing pocket books and Health Education about Menarche and menstrual preparation. The results achieved were an increase in knowledge between before and after providing Health Education. The output of this activity is increasing youth knowledge, IPR Activity Videos, pocket books with ISBN and journal publications.